Factors affecting pre-failure instability of sand under plane-strain conditions - Wanatowski, D.; Chu, J. (Thomas Telford (ICE Publishing), 2012)
Experimental data obtained from a plane-strain appara- tus are presented in this paper to show that a pre-failure instability in the form of a rapid and sustained increase in strain rate can occur for both contractive and dilative sand under fully drained conditions. However, this type of instability is different from the runaway type of instability observed under undrained conditions, and has therefore been called conditional instability. Despite the differences, the conditions for both types of instability are the same for contractive sand. There are also other factors that affect the pre-failure instability of sand ob- served in the laboratory. These include the stress ratio, void ratio, sand state, load control mode and reduction rate of the effective confining stress. In this paper, these factors are discussed and analysed using experimental data obtained from undrained instability (or creep) tests and constant shear drained (CSD) tests carried out under plane-strain conditions.